Effect of Integrated Physical Activities with Mathematics on Objectively Assessed Physical Activity - Spyridoula Vazou; Pedro F. Saint-Maurice; Miriam Skrade; Gregory Welk (MDPI AG, 2018)
Background: One of the promising strategies for increasing physical activity (PA) at school is to integrate it with academic learning. The purposes of this study were: (a) to examine differences in objectively measured PA levels between integrated PA with mathematics and traditional lessons, and (b) to evaluate the PA levels of different integrated PAs. Methods: Seventy-seven 4th grade students (41 males) were included in an intervention (Move for Thought program: M4T) group (n = 46) that utilized PA integrated with mathematics or a control group (n = 31). Accelerometer data from each student were collected during five complete school days. M4T and control classroom sessions were identified using teachers’ logs. Accelerometer data were extracted, processed separately, and aggregated into a single data set. Minutes and percent time at different PA intensities were obtained using accelerometer minute-by-minute predicted METs. Results: One-way ANOVAs on PA levels showed a significant group effect (F = 5.33, p < 0.05) on moderate-to-vigorous PA (MVPA) in favor of the M4T group, but not on sedentary and light PA. The most active integrated PA provided 10.88 min of MVPA (SD = 11.87; 21.38 ± 24.38%) in a 50 min class period. Conclusion: Integrating PA with mathematics in the classroom can contribute to increasing MVPA levels in children.